(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: The therapeutic use of oxygen under pressure is known as hyperbaric oxygen therapy (HBOT) and has been used to assist wound healing for almost 40 years. The purpose of the present study was to see the outcome of hyperbaric oxygen therapy following its use in non healing wounds. Methods: This prospective observational study was conducted in the Department of Plastic Surgery, Dhaka Medical College Hospital, Dhaka, from March 2016 to February 2017 for a period of 12 (twelve) months. The study was carried out on patients with non healing wounds. Patients were initially assessed with detailed history, clinical examination and investigations, and then treated with hyperbaric oxygen therapy for 90 minutes per session in 6 days a week for 25 cycles. Wound was assessed clinically, and with transcutaneous oximetry and laboratory investigations. Results: Eighty patients were included, where 52 (65.0%) patients had diabetic ulcer, followed by post traumatic wound (14) and venous ulcer (7). Fifty nine (73.75%) patients had initial wound size of < 50 cm2 with mean size 14.78 ± 12.5 cm2. Wound size reduction rate after 15 cycles of HBOT was 42.78%, and after 25 cycles of HBOT it was 61.21%. Among the 80 patients, 60 (75.0%) had moderate amount of discharge before HBOT; 19 (31.67%) & 25 (41.67%) reduced to small & no discharge after 25 cycles of HBOT respectively. 39 (48.75%) patients had serosanguineous discharge before HBOT, followed by 36 (45.0%) and 5 (6.25%) patients with purulent and serous discharge. Among the 39 patients with serosanguineous discharge, 15 (38.46%) & 20 (51.28%) patients had serous & no discharge after 25 cycles of HBOT respectively. Before starting HBOT, mean transcutaneous oximetry was 58.26 ± 3.84 mmHg, and it was 62.1 ± 6.27 mmHg and 66.92 7.52 mmHg after 15 and 25 cycles of HBOT respectively. Conclusion: So it can be stated that the hyperbaric oxygen therapy is a good option in treating different non healing wounds. J Bangladesh Coll Phys Surg 2019; 37(3): 109-118